LOCAL SUPPORT FOR FESTIVALS AS TOURISM PRODUCTS: A SYSTEMATIC REVIEW (Journal of Event, Tourism and Hospitality Studies, 2025)
This paper reviews the formation of locals’ support towards festival as tourism product. This study will provide a clear idea on the connection between locals and festivals at a particular tourism destination. Current literatures show that locals’ support towards tourism product is fostered by various antecedents such as economic gains, perceived benefits, level of community attachment, active local participation, quality of life, as well as locals’ attitude towards tourism development. Methodologically, this paper aims to systematically review past studies to produce a holistic understanding on the antecedents of locals’ support towards festival as tourism product. For the purpose of this study, the authors examined databases such as Scopus, Science Direct, and Google Scholar to select related articles. Articles selected manually from Google Search were also included. All the related articles were subjected to a thorough and systematic quantitative review and content analysis. By identifying the main research gaps, the paper proposes a new model of antecedents for locals’ support towards festival as tourism product. Finally, this paper provides theoretical implications based on the gaps in previous research. Furthermore, it also offers valuable insights in promoting locals’ support for festival development. Essentially, the results of this study using systematic literature review, provides a complete summary of antecedents that form locals’ support towards festival tourism product.Keywords: Local support, festivals, tourism product, systematic literature review